Changes in knee extension peak torque and body composition and their relationship with change in gait speed. Issue 5 (4th July 2019) - Osawa, Yusuke; Chiles Shaffer, Nancy; Shardell, Michelle D.; Studenski, Stephanie A.; Ferrucci, Luigi
Abstract: Background: Slow gait speed is a powerful predictor of disability in activities of daily living and mortality. Muscle strength and body composition change over time, but their changes differ by sex. How these parameters jointly affect gait speed decline is unknown. Understanding this association could help develop and evaluate the sex‐specific effects of lifestyle interventions to delay gait speed decline in older adults. We assessed whether changes in strength (Δstrength), appendicular lean mass (ΔALM), and fat mass (Δfat) jointly relate to change in gait speed and whether the association differs by sex. Methods: The analytic sample comprised 575 women and 539 men aged 22–95 years enrolled in the Baltimore Longitudinal Study of Aging. Mean follow‐up was 4.0 years. Measures included isometric knee extension strength, dual‐energy X‐ray absorptiometry‐assessed ALM and fat mass, and gait speed from the 400 m fast pace walk. Sex‐specific linear mixed models were adjusted for follow‐up time and baseline age, race, height, ALM, fat mass, peak torque, and gait speed. We also included second‐order interaction terms of the key predictive variables (e.g. Δstrength × ΔALM). To interpret the interactions, we estimated average gait declines using the 25th or 75th percentile of the two significant predictive variables and then assessed which condition relates to larger decline in gait speed. Results: In both sexes, independent of ΔALM and Δfat, larger decline in strength significantly related to larger decline in gait speed ( P = 0.01 for both sexes). In men, interactions between Δstrength × ΔALM and Δfat by ΔALM were associated with change in gait speed; men with greater declines in both muscle strength and ALM or greater declines in both ALM and fat have steeper gait speed decline. In contrast, in women, the interaction between Δfat and ΔALM was associated with change in gait speed; women with an increase in fat mass combined with less decline in ALM have steeper gait speed decline. Conclusions: While change in strength affects change in gait speed in both sexes, the effects of body composition change differ by sex. Dual‐energy X‐ray absorptiometry‐based estimates of lean mass may be confounded by intramuscular fat. Future studies should examine sex‐specific combined effects of change in strength and body composition on mobility using multiple techniques to measure body composition. Intervention studies should consider testing sex‐specific interventions on body composition.